Penerapan Metode OCRA dalam Menentukan Media Pembelajaran Online Terbaik di Masa Pandemi Covid-19 dengan Pembobotan ROC - Dwina Pri Indini; Khairunnisa Khairunnisa; Nola Dita Puspa; Tesa Aurelia Siregar; Mesran Mesran, M.Kom (STMIK Budi Darma, 2021)
Right now the Covid-19 pandemic is very troubling where people must comply with regulations that have been made by the government, namely reducing non-essential activities outside the home so that there are no crowds, at this time many educational institutions are closed for face-to-face learning activities and then online or online learning is applied. online. In this online learning there are many media that can be used so that it makes teachers and students confused to determine which media is the most appropriate to use. This study uses a Decision Support System as a system in selecting which online learning media is the best. In determining the best online learning media, it must meet criteria such as User Capacity, Visual Interaction, Friendly Features, Application Features and Internet Data Usage. Therefore, a Decision Support System (DSS) is needed in solving existing problems by applying the ROC (Rank Order Centroid) and OCRA (Operational Competitiveness Rating Analysis) methods that can generate weight values and preference values from the first ranked alternative. So that the best online learning media during the Covid-19 pandemic lies in the A3 alternative, namely Moodle with a value of 2,296.